Contribution of non-timber forest products in the economy of rural populations in southern Benin: case of edible fungi (Volvariella volvacea and Pleurotus abalonus) in Sakété commune - ALI, Rachad Kolawolé Foumilayo Mandus (My University, 2019)
The production of Pleurotus abalonu on palm stalks and that of Volvariella volvacea on dead palm trees is very little known in Benin. However, few studies have been conducted on these means of production. The purpose of this study is to generate useful information to take advantage of the potential of these non-ligneous forest products. The sample includes 88 respondents, including Pleurotus abalonus producers (9.09%), Volvariella volvaceapickers (88.63%) and hotel and restaurant managers (11.36%). Data collection is based on structured interviews and direct observations. The stakeholders involved in this product include, among others, growers of Pleurotus abalonus, the collectors of Volvariella volvacea, wholesalers and consumers. The marketing of these mushrooms produced and collected brings significant income to these stakeholders. A producer of Pleurotus abalonus earns on average 202.410 F CFA, after the production of 200 kg of mushrooms in three months. The income of a Volvariella volvaceaseller varies between 2000 and 4000 F CFA per day for 1 to 2 kg of Volvariella volvacea picked. The consumption of these, allows the population to fight against protein deficiency and certain diseases such as anemia, thanks to the nutrients they have. The valorization of the production of mushrooms (Pleurotus abalonus and Volvariella volvacea) on stems and dead palms, through awareness, training and supervision, are the essential points for the development of this crop.
Keywords: Sakete; production; edible mushrooms; palm crawl; dead palm